1988
DOI: 10.1007/bf00970770
|View full text |Cite
|
Sign up to set email alerts
|

Regional distribution of dopamine, 5-hydroxytryptamine, and noradrenaline in the rat vas deferens

Abstract: The concentrations of dopamine (DA), 5-hydroxytryptamine (5-HT) and noradrenaline (NA) in the rat vas deferens divided in eight or four sections were determined by high performance liquid chromatography with electrochemical detection. Dopamine and NA had the same regional distribution; their concentrations were maximal near the prostatic end and decreased towards the epididymis. The concentration of 5-HT also decreased from the prostatic to the epididymal end, but 5-HT did not follow the same regional distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Fuenmayor et al [20] and Celuch and Sloley [21] described the presence and release of serotonin, dopamine and noradrenalin (NA) from rat vas deferens. It is conceivable that protection from hypothermia in SMAC cells is dependent on the cellular uptake of serotonin, in view of the failure of its protection in the presence of an SSRI and the unchanged effectiveness of serotonin in the presence of the non-selective 5-HT 2 receptor blocker ketanserin.…”
Section: Discussionmentioning
confidence: 99%
“…Fuenmayor et al [20] and Celuch and Sloley [21] described the presence and release of serotonin, dopamine and noradrenalin (NA) from rat vas deferens. It is conceivable that protection from hypothermia in SMAC cells is dependent on the cellular uptake of serotonin, in view of the failure of its protection in the presence of an SSRI and the unchanged effectiveness of serotonin in the presence of the non-selective 5-HT 2 receptor blocker ketanserin.…”
Section: Discussionmentioning
confidence: 99%
“…In the epididymis, sperm achieve the capacity to move (Robaire & Hermo 1988) and undergo changes in the cytoplasmic membrane (Shalgi et al 1989). Serotonin is present in the epididymis (Leung et al 1999) and vas deferens (Celuch & Sloley 1988), but its function is not known.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that dopamine (DA) and noradrenaline (NE) coexist in the same sympathetic neurons of the rat vas deferens. Concentrations of DA and NE are maximal near the prostatic end and decrease toward the epididymis [6]. Also, dopamine-betahydroxylase (DBH), an enzyme that converts DA to NE, has been shown to be present in the NE-and peptide-containing nerves in the epididymis of the boar [7,8].…”
Section: Introductionmentioning
confidence: 99%